2016
DOI: 10.21037/jgo.2016.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Ga-68 DOTANOC PET/CT imaging in detection of primary site in patients with metastatic neuroendocrine tumours of unknown origin and its impact on clinical decision making: experience from a tertiary care centre in India

Abstract: Background: Neuroendocrine tumours (NETs) are rare, heterogeneous group of tumours which usually originate from small, occult primary sites and are characterized by over-expression of somatostatin receptors (SSTRs). Positron emission tomography/computed tomography (PET/CT) using Ga-68-labeledsomatostatin-analogues have shown superiority over other modalities for imaging of NETs. The objective of the study was to retrospectively evaluate the efficacy of Ga-68 DOTANOC PET/CT imaging in detecting the primary site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In our study, the positive rates of Syn, NSE, CgA and AFP were separately 64.19%, 29.63%, 46.91% and 9.88% and there was no difference between the groups. It is reported 15 , 16 that the majority of the PHNETs occurred in the right lobe of the liver and the metastatic HNETs were proven to show a clinical tendency of the presentation of multifocality. We found that the III segment of the liver was the mostly-occurred site for the HNETs and there was no difference for the rate of multifocality between the groups (P=0.539).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the positive rates of Syn, NSE, CgA and AFP were separately 64.19%, 29.63%, 46.91% and 9.88% and there was no difference between the groups. It is reported 15 , 16 that the majority of the PHNETs occurred in the right lobe of the liver and the metastatic HNETs were proven to show a clinical tendency of the presentation of multifocality. We found that the III segment of the liver was the mostly-occurred site for the HNETs and there was no difference for the rate of multifocality between the groups (P=0.539).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were continuously made to identified the HNETs, Ankur 16 has reported the imaging features from Ga-68 PET/CT in 68 metastatic HNETs patients and indicated that Ga-68 PET/CT is a promising imaging modality in clinical practice for identifying the primary site of the HNETs, while some other scholars have analyzed 38 cases of PHNET with the dynamic contrast-enhanced CT findings, indicating that of which 74% of the lesions in the arterial phase were enhanced, 52% were found with delayed enhancement and 48% showed hepatocellular carcinoma-like enhancement 17 . Besides, Xiaoqi 18 suggested that the CDX-2 and TTF-1 expression in the specimen is highly specific in identifying the origin of NETs.…”
Section: Discussionmentioning
confidence: 99%
“…7 The NETs are characterized by the overexpression of somatostatin receptors (SSTRs). 8 Apart from malignant cells, these receptors are expressed by inflammatory cells and cells of the innate and adaptive immune system. 9 The SSTRs signal to alter hormonal secretion, augment apoptosis, and reduce cellular proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…PET/ CT with 68 Ga-DOTATATE plays a pivotal role in neuroendocrine tumor (NET) management (1), providing incremental data compared with 111 In-pentetreotide (Octreoscan; Mallinckrodt) and conventional imaging (2) and better sensitivity and specificity than 18 F-FDG PET imaging for neuroendocrine neoplasms (3,4). The clinical indications include primary tumor localization (5), metastatic disease detection, and response monitoring (6). In addition, somatostatin receptor (SSTR) imaging has established value in the prediction of response to treatment (7).…”
mentioning
confidence: 99%